KAJIAN POPULASI Anophelesspp 01 OAERAH ENOEMIS MALARIA (Studi Kasus di Oesa Gedangan Kecamatan Tegalombo Kabupaten Pacitan) - Tria Kusuma Praja; Irwan Sulistio; Marlik . (Poltekkes Kemenkes Surabaya, 2013)
Pacitan district are malaria endemic areas. Built in that area still has a high malariacases. There were 432 cases in 2010 and there were 233 cases in 2011 at the area. Thenumber of cases malaria in sub Tegalombo were 23 Cases. Purpose of this study was todescribe the Anopheles spp populations in the sub district Tegalombo Pacitan at 2013.The research was an observational research, it was cross-sectional study. The data wasconducted through observation, measurement, counting and examining laboratory.Anopheles spp in Tegalombo District was An.sconltus, An. vagu An.ermateas.An.berbrostris, An.subpictus, An.kochi, An.maculatus and An.teselatus. The most of thepopulation was An. vagus. Anopheles spp had higt biting activity 23.00-24.00 pm. Eight spesiesAnopheles spp have blood seeking behavior outside the home (eksofagik) and resting behavioroutside the home (eksofilik).It will be required confirmation of Anopheles vagus as vector malaria disease. Thesociety should be using long sleeves for their activity, and using net for their sleeping time. Itis necessaryto explain the risk of malaria transmission and prevention of it.Key word: Community of Anopheles spp and behavior of Anopheles spp.